Frequency analysis on pulse train of lightning discharge observed in Malacca, Malaysia - Ramlee, N.A.; Ahmad, N.A.; Esa, M.R.M.; Baharudin, Zikri Abadi (2023)
Pulse train of lightning discharge is an intracloud event that remains poorly understood especially in Malaysia. Therefore, this paper presents the frequency analysis on pulse train observed in Malacca, Malaysia. This study employed 100 pulse train samples preceding negative subsequent return stroke to be analyzed through wavelet analysis in order to investigate their power spectrum characteristics. All the samples were superimposed with the dart leader of subsequent return stroke. In this regard, the wavelet analysis was employed in this study to investigate the range of power produced by pulse train and the frequency regions of their occurrences. The scalogram of the pulse train signal was produced by using the Mexican Hat wavelet function in Matlab. The spectral and spread frequency regions were measured from the scalogram. In this study, the pulse train samples radiate energy at a range of 7.7 kHz to 403.2 kHz. As for the maximum peak power, the average pulse train generated was 184.6 (V/m)² and can reach up to 2170 (V/m)². These findings enhanced the understanding of lightning physics, particularly on the pulse train characteristics of lightning in Malaysia.